Influence of Cinnamon Supplementation on Liver Enzymes in Male Rabbits - Amani Salem; Marwa Abdullah; Fayrouz Khaled; Marwa Mohammd (AlQalam Journal of Medical and Applied Sciences, 2024)
The liver, a vital organ in the body, plays a central role in managing the metabolism of both internal and external substances. It is crucial for drug processing and detoxification; however, it is vulnerable to damage from foreign chemicals, alcohol intake, poor nutrition, environmental pollutants, illnesses, and various medications. Besides being commonly used as a spice, the inner bark of cinnamon (Cinnamomum zeylanicum L.) has gained popularity for its applications in disease prevention and treatment. Current evidence has indicated potential health benefits associated with cinnamon intake; however, its effects on liver function remain unclear. Therefore, this systematic review and meta-analysis aimed to investigate the effects of cinnamon supplementation on liver enzymes in male rabbits. Relevant studies were identified through a comprehensive search of PubMed/Medline, Scopus, Web of Science, Cochrane Library, and Embase databases up to September 2023. Ten male New Zealand White rabbits were randomly divided into two groups: (1) a control group, and (2) a group treated with cinnamon at a dose of 200 mg/kg body weight. Blood samples and liver homogenates were used to assess liver function markers in both serum and liver tissue. The results showed that cinnamon treatment led to a significant (P<0.05) reduction in the activity of blood plasma and liver enzymes "LDH", "AST", and "ALT", while "ALP" and "AcP" levels significantly (P<0.05) increased compared to the control group. Further high-quality studies are necessary, especially in populations with abnormal liver enzyme levels, to more definitively establish the clinical efficacy of cinnamon on liver function. يلعب الكبد، وهو عضو حيوي في الجسم، دورًا محوريًا في إدارة عملية التمثيل الغذائي للمواد الداخلية والخارجية. وهو أمر بالغ الأهمية لمعالجة الأدوية وإزالة السموم؛ ومع ذلك، فهو عرضة للتلف الناتج عن المواد الكيميائية الغريبة، وتناول الكحول، وسوء التغذية، والملوثات البيئية، والأمراض، والأدوية المختلفة. بالإضافة إلى استخدامه بشكل شائع كتوابل، اكتسب اللحاء الداخلي للقرفة شعبية لتطبيقاته في الوقاية من الأمراض وعلاجها. أشارت الأدلة الحالية إلى فوائد صحية محتملة مرتبطة بتناول القرفة؛ ومع ذلك، لا تزال آثارها على وظائف الكبد غير واضحة. لذلك، تهدف هذه المراجعة المنهجية والتحليل التلوي إلى التحقيق في آثار مكملات القرفة على إنزيمات الكبد لدى الأرانب الذكور. تم تحديد الدراسات ذات الصلة من خلال بحث شامل في عدة قواعد بيانات حتى سبتمبر 2023. تم تقسيم عشرة أرانب بيضاء من نيوزيلندا بشكل عشوائي إلى مجموعتين: (1) مجموعة تحكم، و(2) مجموعة عولجت بالقرفة بجرعة 200 ملغ. ملجم/كجم من وزن الجسم. تم استخدام عينات الدم ومتجانسات الكبد لتقييم علامات وظائف الكبد في كل من المصل وأنسجة الكبد. أظهرت النتائج أن علاج القرفة أدى إلى انخفاض كبير (P<0.05) في نشاط بلازما الدم وإنزيمات الكبد "LDH" و"AST" و"ALT"، بينما ارتفعت مستويات "ALP" و"AcP" بشكل كبير (P<0.05) مقارنة بمجموعة التحكم. هناك حاجة إلى مزيد من الدراسات عالية الجودة، وخاصة في السكان الذين يعانون من مستويات غير طبيعية من إنزيمات الكبد، لتحديد الفعالية السريرية للقرفة على وظائف الكبد بشكل أكثر دقة"